Exploring environmentally responsible behavior of megaproject contractors using an extended theory of planned behavior - Zhao Zhai; Shirong Gao; Ming Shan (Scientific Reports)
Abstract Environmentally responsible behavior (ERB) of contractors in megaprojects is crucial for promoting sustainability, but how to trigger and predict it remains unclear. This study integrates moral identity and corporate green culture into the theory of planned behavior (TPB) to develop an extended TPB (ETPB). Based on a questionnaire survey (N = 181) from Chinese megaprojects, we found that (1) contractors’ attitudes, subjective norms, and perceived behavioral control positively influence their intentions to engage in ERB; (2) perceived behavioral control, intentions, moral identity, and corporate green culture positively influence ERB; and (3) the explanatory power (R 2) and predictive power (PLSpredict, CVPAT) of the ETPB model are superior to those of the TPB model. These findings offer novel theoretical insights through the ETPB model in the context of megaprojects and provide practical guidance for promoting ERB among contractors.